How Scoop Affect the Credibility of News through Social Media? An Empirical Study - Rosli, Mohammed; Nik Adzrieman, Abdul Rahman; Lee, Jun Choi (AENSI Publication, 2017)
Background: There is a ground shift happening in media industry, not just in news, because of the widening reach of social media. The use of Social Networking Sites (SNSs) in journalistic work ha s been a core concern for journalists. Scoop is sophisticated phenomena in media, which is associated with credibility. Objective: To verify empirically of this phenomenon, this study examined how scoop affect the credibility of the news on SNSs. This quantitative study presents and discusses empirical findings from a survey of 242 Jordanian journalists by questionnaire. Results: The results indicate that scoop always pushes journalists to communicate with sources that have a high level of quality and honesty to get real information. In addition, the results of this study provide positive evidence about the importance of scoop in maintaining the credibility of the news, journalist, and media, due to the ongoing verification of the sources that provide news to journalists. Therefore, the application of credibility criteria in dealing with news on social media contribute to the organization of this media phenomenon to become more useful to journalists and society. Conclusion: The competition among journalists to get the news before others, and the increased use of social networking sites as a source of news, will contribute to maintaining the use of scoop among journalists, especially given that citizens needing to know everything in the fastest time and from credible sources. Journalists and media organizations in Jordan should pay attention to new phenomena associated with the rapid developments in media work.